Search for nucleon decay with final states l+η0, ν̄η0, and ν̄π+,0 using Soudan 2 - Wall, D; Allison, W; Alner, G; Ayres, D; Barrett, W; Bode, C; Border, P; Cobb, J; Cotton, R; Courant, H; Chung, J; Demuth, D; et al. (2000)
We have searched for nucleon decay into five two-body final states using a 4.4 kiloton-year fiducial exposure of the Soudan 2 iron tracking calorimeter. For proton decay into the fully visible final states μ+η0 and e+η0, we observe zero and one event, respectively, that satisfy our search criteria for nucleon decay. The lifetime lower limits (τ/B) thus implied are 89×1030 years and 81×1030 years at 90% confidence level. For neutron decay into ν̄η0, we obtain the lifetime lower limit 71×1030 years. Limits are also reported for neutron decay into ν̄π0, and for proton decay into ν̄π+. ©2000 The American Physical Society.